The sharing economy: can registered homestay operators survive the challenges ahead? - Mohamad Nor, Sarina; Awang, Khairil Wahidin; Ismail, Normazwana; Samdine, Zaiton; Mohammad Afand, Syamsul Herman (Primrose Hall Publishing Group, 2019)
Can registered homestay operators survive in a sharing economy or will it sink? The peer-to-peer marketplace, collectively known as the sharing economy, for example Airbnb has emerged as an alternative supplier of the conventional accommodation business models overhauling the traditional business concept. This paper explores the disruptive impacts of the sharing economy on MOTAC’S traditional homestay business concept and whether the registered homestay operators in Selangor, Malaysia can survive the challenges ahead. The question of how disruptive a sharing economy is and the effect on MOTAC’s homestay business is a big concern. This study is exploratory in nature, using the snowballing technique of collecting data. A qualitative approach was applied, and the primary data was gathered through field observations and in-depth interviews with selected stakeholders. The results of this study reveal that registered homestay operators suffer from various challenges. Not all registered homestay operators receive sufficient homestay income after a long involvement in MOTAC homestay business which lead more registered homestay operators to withdraw from registration. This study contributes to an in-depth understanding of the factors that impede registered homestay operator’s success in a sharing economy. Therefore, this study not only recommends the importance of collaboration and partnership among tourism stakeholders that enable registered homestay operators to survive the challenges ahead towards sharing economy but also sheds new light on the real effects of the sharing economy and provides important policy implications for policymakers.